The effect of the roles of clinical educators on patient safety competencies in nursing profession students - Dyah Wiji Puspita Sari; Yuni Sufyanti Arief; Ahsan; Muhammed Abdurrouf (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the correlation between clinical educator roles and patient safety competence in nursing students. Method:The cross-sectional study was conducted from December 21, 2021, to June 7, 2022, at the Sultan Agung Teaching Hospital, Semarang City, Central Java, Indonesia, and comprised nursing students in the clinical stage of their training. Data was collected using an observation sheet, while the role of clinical educator was explored using a structured questionnaire. Data was analysed using SPSS 21. Result: There were 232 nursing students. Of these, 203(87.5%) were females. The age range of the students included was between 21 and 25 years with an average of 23.14±0.543 years. All the students were hospital oriented and had received training on patient safety measures. Patient safety competencies were related to the roles of resource person (p<0.038), role model (p<0.004), evaluator (p<0.020), facilitator (p<0.006), manager (p<0.013) and supporter (p<0.007). The role of the manager had the most significant effect on patient safety competencies (p<0.001). Conclusions: Patient safety competencies were significantly related to the roles of resource person, role model, evaluator, facilitator, manager and supporter, but the role of the manager had the strongest correlation with patient safety competencies. Keywords: Students, Nursing, Patient Safety, Surveys, Questionnaires, Hospitals, Teaching, Evaluator, Facilitator, Supporter